Reversal of dysthyroid optic neuropathy following orbital fat decompression. Issue 6 (1st June 2000) - Kazim, Michael; Trokel, Stephen L; Acaroglu, Golge; Elliott, Alexandra
Abstract : AIMS: To document the successful treatment of five patients with dysthyroid optic neuropathy by orbital fat decompression instead of orbital bone decompression after failed medical therapy. METHODS: Eight orbits of five patients with dysthyroid optic neuropathy were selected for orbital fat decompression as an alternative to bone removal decompression. Treatment with systemic corticosteroids and/or orbital radiotherapy was either unsuccessful or contraindicated in each case. All patients satisfied clinical indications for orbital bone decompression to reverse the optic neuropathy. High resolution computerised tomographic (CT) scans were performed in all cases and in each case showed signs of enlargement of the orbital fat compartment. As an alternative to bone decompression, orbital fat decompression was performed on all eight orbits. RESULTS: Orbital fat decompression was performed on five patients (eight orbits) with optic neuropathy. Optic neuropathy was reversed in all cases. There were no cases of postoperative diplopia, enophthalmos, globe ptosis, or anaesthesia. All patients were followed for a minimum of 1 year. CONCLUSIONS: In a subset of patients with an enlarged orbital fat compartment and in whom extraocular muscle enlargement is not the solitary cause of optic neuropathy, fat decompression is a surgical alternative to bony decompression.